2012
DOI: 10.5007/1980-0037.2012v14n4p363
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento físico e estado nutricional de escolares do Vale do Jequitinhonha, Minas Gerais, Brasil.

Abstract: -The study analyzed physical growth and nutritional status in a representative sample of schoolchildren from the Jequitinhonha Valley region, Minas Gerais, Brazil. A total of 5100 subjects (2730 girls and 2370 boys) aged 6 to 18 years were included in the study. Nutritional status of the under-10 group was assessed by z < -2 for weight-for-height and height-for-age (undernutrition) and by z > +2 for weight-for-height (overweight). For children over 10, the 5 th and 85 th percentiles of weight for age were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
2
1
0
4
Order By: Relevance
“…In the present study, the prevalence of overweight and obesity followed a similar trend in the two genders, decreasing gradually with increasing age. This trend has also been reported in another study 16 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the prevalence of overweight and obesity followed a similar trend in the two genders, decreasing gradually with increasing age. This trend has also been reported in another study 16 .…”
Section: Discussionsupporting
confidence: 90%
“…However, we found epidemiological studies conducted in Brazil that used similar criteria: age, BMI and IOTF. Prevalence rates of overweight [14][15][16][17] and obesity 14,15,[17][18][19] similar to those observed here have been identified in at least one of the genders. When the prevalence estimates of overweight and obesity were summed to determine the total prevalence of excess weight, some studies 14,15,17,19 reported values exceeding 20%, as observed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Por fim, o IMC foi classificado de acordo com a proposta de Cole et al 15 . Esta proposta tem sido amplamente utilizada tanto no âmbito nacional [1][2][3][16][17][18] , quanto internacional [19][20][21][22] , facilitando a comparação dos resultados encontrados aos de outros estudos. Contudo, é preciso considerar que se outras propostas de classificação do IMC fossem utilizadas, prevalências de excesso de peso mais altas poderiam ser encontradas, pois alguns estudos 18,19 tem indicado que as prevalências de sobrepeso e obesidade são menores quando a proposta de Cole et al 15 é utilizada.…”
Section: Discussionunclassified
“…Com relação às frequências de excesso de peso, os resultados são coerentes com aqueles encontrados por estudos realizados em cidades de diferentes regiões do país [1][2][3][16][17][18] que utilizaram a mesma proposta de classificação do IMC, indicando que as prevalências tendem a ser mais altas no sul do país que nas demais regiões 1,17,18 . Tais resultados revelam uma situação preocupante, pois prejuízos à saúde decorrentes do excesso de peso corporal podem ser observados já nos anos da adolescência 5,26 .…”
Section: Discussionunclassified
“…A maioria dos estudos sobre o tema tem sido realizada com menores de cinco anos, o que destaca a necessidade de pesquisas que envolvam crianças em idade escolar. Avaliar a desnutrição em escolares com enfoque direcionado ao déficit de estatura é importante por proporcionar uma visão ampliada em relação ao estado de saúde individual e coletivo 6,7 . Observa-se, também, que entre as crianças de seis a dez anos de idade as prevalências de desnutrição infantil vêm diminuindo, enquanto que os casos de sobrepeso constituem condição nutricional em ascensão 8,9 .…”
Section: Introductionunclassified